2019
DOI: 10.1007/s00170-019-03711-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyoptimisation of the refill friction stir spot welding parameters applied in joining 7075-T6 Alclad aluminium alloy sheets used in aircraft components

Abstract: In the aerospace industry, the refill friction stir spot welding (RFSSW) method is increasingly used to join thin sheets, especially those made of 2xxx and 7xxx series aluminium alloys. This paper presents the results of spot welding lap joints of 7075-T6 aluminium alloy sheets. The load capacity of joints was determined by tensile/shear tests using a universal testing machine. The effect of tool plunge depth, tool rotational speed and duration of welding on joint load capacity and failure mode was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…A similar result has been reported by Tier et al [8]. Kluz et al [9] found that tool rotation speed has the greatest impact on the load-carrying capacity of the refill FSSW joint for 7075 aluminum alloys. Defects are the main factors to influence the formation and mechanical properties of joints.…”
Section: Introductionsupporting
confidence: 84%
“…A similar result has been reported by Tier et al [8]. Kluz et al [9] found that tool rotation speed has the greatest impact on the load-carrying capacity of the refill FSSW joint for 7075 aluminum alloys. Defects are the main factors to influence the formation and mechanical properties of joints.…”
Section: Introductionsupporting
confidence: 84%
“…The values of the welding parameters are crucial in assuring the fabrication of welds without defects such as voids in the weld corner, bonding ligament, and structural discontinuities. The RFSSW parameters were selected based on the authors' experience and the results of previous investigations of the authors presented in the paper [37]. The first stage of the poly-optimisation of the values of welding process parameters was focused on the analysis of the tool plunge depth g on the load capacity of the joint.…”
mentioning
confidence: 99%
“…The values of the parameters that were selected assured the most favourable joint quality in terms of the highest static strength and quality of the weld structure (minimum number of structural discontinuities, structural notches, as small as the heat affected zone, etc.) [37].…”
mentioning
confidence: 99%
“…When the plunge depth was restricted to the upper sheet, the hooking feature was not found to be significant to affect the joint static shear strength [8]. The results of 7075 Al joints showed that significantly better weld properties were obtained by increasing the dwell time [39].…”
Section: Similar Alloys Jointsmentioning
confidence: 90%